Community pharmacists’ role towards preventing abuse or misuse and dependence of codeine-containing analgesic medications in Saudi Arabia: a multicenter cross-sectional study - Alanazi, Muteb; Ansari, Mukhtar; Alharby, Tareq Nafea (Frontiers in Pharmacology, 2024)
The misuse, or abuse, and dependence of medications containing codeine continues to be a major global public health concern. This study aimed to investigate the role of community pharmacists in preventing the abuse or, misuse, and dependence of codeine-containing analgesic drugs in Saudi Arabia.A cross-sectional study involving 226 community pharmacists from various community pharmacies across multiple cities of Saudi Arabia was conducted from 09 May 2023 to 09 October 2023. Study data were collected and managed using Research Electronic Data Capture tool. Fourteen trained data collectors visited randomly selected community pharmacies in different cities, provided pharmacists with an electronic questionnaire link, and collected their responses electronically. The dataset was downloaded in SPSS format, and analyzed for both descriptive and inferential purposes.The primary indicators that community pharmacists considered when suspecting cases of abuse or, misuse, and dependence included customers who requested a larger quantity of the medication (88.5%), frequently visited the pharmacy and sought the specific medicine (82.7%), and those who took advantage of the crowd (70.8%). Pharmacists have been instrumental in preventing abuse, or misuse, and dependence by ensuring that medicines with abuse potential are not easily accessible to consumers (87.6%), providing alternative options (81%), reducing the dose (65%), referring patients to physicians (62.4%), and refusing to sell or denying availability (54.9%). Additionally, pharmacists primarily focused on raising public awareness (85%) as a noteworthy proportion of customers (54.9%) became desperate to obtain the drug after missing a dose. It was also suggested that community pharmacists should receive specialized training in substance abuse or misuse, as 46.9% of them lacked such training.Discussion: Community pharmacists, being frequently the initial point of contact easily reachable, possess the capability to greatly assist in identifying the abuser patients and averting abuse or,